MENINGKATKAN KETERAMPILAN BALL CONTROL SEPAK BOLA MELALUI MEDIA DINDING - DEKA ISMI MORI SAPUTRA; Ade Eka Putra (Jurnal Muara Olahraga, 2019)
Abstract: The study used a Class Action Research design which was carried out in two cycles, each cycle consisting of planning, action implementation, observation and reflection. The subjects of this research were Class V Students of SDN 43 / II Tanjung Belit, Jujuhan District with a total of 20 students. Data on the results of soccer learning are obtained through performance tests, observation sheets are used to collect data on student activities in following the learning process of Football Ball Control Through Wall Media.The results of this study were obtained based on an assessment of three aspects, namely psychomotor, affective, and cognitive. From the results of the assessment, there was an increase in learning outcomes from cycle I to cycle II. In the first cycle 55.00% in the complete category, the number of students who completed was 11 students. In cycle II there was an increase in students in the completion category by 85.00%, with the total number of students completing 17 students out of the total number of students. Based on the results of the study it was concluded that learning Soccer Ball Control Through Wall Media can improve student learning outcomes in Class V SDN 43 / II Tanjung Belit Jujuhan District. And for Physical Education teachers in Elementary Schools can apply learning with Wall Media in Physical Education lessons especially in soccer learning.